2012
DOI: 10.1016/j.drugalcdep.2011.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Randomized multi-site trial of the Job Seekers’ Workshop in patients with substance use disorders

Abstract: Background Unemployment is associated with negative outcomes both during and after drug abuse treatment. Interventions designed to increase rates of employment may also improve drug abuse treatment outcomes. The purpose of this multi-site clinical trial was to evaluate the Job Seekers’ Workshop (JSW), a three session, manualized program designed to train patients in the skills needed to find and secure a job. Method Study participants were recruited through the NIDA Clinical Trials Network (CTN) from six psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 40 publications
0
33
1
Order By: Relevance
“…28) and others reported no intervention effects on key employment outcomes (e.g. 22). These inconsistent findings are further complicated by differences in study design and employment measures.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…28) and others reported no intervention effects on key employment outcomes (e.g. 22). These inconsistent findings are further complicated by differences in study design and employment measures.…”
Section: Discussionmentioning
confidence: 74%
“…Another study examining long-term substance abuse treatment clients and methadone maintenance found that neither group experienced any significant improvement in employment (21). More recently, a multi-site randomized trial of the Job Seekers' Workshop found no difference in 12-week or 24-week employment outcomes, with only modest employment gains overall (22).…”
Section: Introductionmentioning
confidence: 93%
“…While the Therapeutic Workplace was in operation the Therapeutic Workplace participants reported significantly more days worked per month, more employment income, more total income, and less money spent on drugs (Table 3). Although much of the employment reported by Therapeutic Workplace participants was employment in the Therapeutic Workplace data entry business, these data show that this population rarely becomes employed in community jobs (Usual Care Control participants), but they will work fairly consistently when given an employment opportunity (Therapeutic Workplace participants) and when common barriers to employment (Svikis et al 2012) are minimized.…”
Section: 0 Discussionmentioning
confidence: 82%
“…Employment has been extremely difficult to promote in low-income adults with long histories of drug addiction (Magura, Staines, Blankertz, & Madison, 2004; Svikis et al 2012). One fairly large and well-conducted study evaluated the long-term effectiveness of an intensive case management intervention in 302 substance-dependent women receiving Temporary Assistance for Needy Families (Morgenstern et al, 2009).…”
Section: 0 Discussionmentioning
confidence: 99%
See 1 more Smart Citation